Preparation And Characterization Of Solid Lipid Nanoparticles For Topical Delivery Of Curcumin - Sundar, Vankayala Devendiran; Dhanaraju, Magharla Dasaratha; Vadaga, Anilkumar; Venkatesh, Midde (Journal of Neonatal Surgery, 2025)
Curcumin, a potent natural polyphenol, exhibits significant therapeutic potential for various inflammatory and skin disorders but faces limitations in bioavailability and stability. To address these challenges, solid lipid nanoparticles (SLNs) were developed as a novel topical delivery system to enhance skin permeation, drug entrapment efficiency, and sustained release properties. This study employed the Box-Behnken design to optimize curcumin-loaded SLNs using Compritol ATO 888, Span 80, and Tween 80 as lipid and surfactant components. Various formulations were evaluated for particle size, polydispersity index (PDI), encapsulation efficiency (EE%), and in vitro drug release behavior. The optimized formulation (F₁₂) demonstrated a particle size of 275.67 nm, a PDI of 0.14, and an encapsulation efficiency of 91.58%, suggesting excellent stability and uniformity. Further drug loading studies (N=3) resulted in a mean ± SD of 15.29 ± 3.56%, confirming high drug entrapment. In vitro drug release studies indicated a sustained release profile, favouring prolonged drug retention in the skin. Excipients such as Compritol ATO 888 provided occlusive effects, enhancing the retention time and bioavailability of curcumin. The study also included Fourier Transform Infrared (FTIR) and Differential Scanning Calorimetry (DSC) analyses, confirming drug-lipid compatibility and stable crystalline structures.